2006
DOI: 10.1051/vetres:2005038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex steroids on the viability and CD11b, CD18 and CD47 expression of blood neutrophils from dairy cows in the last month of gestation

Abstract: -In the period around parturition, cows experience an increased susceptibility for the development of Escherichia coli mastitis. This increased susceptibility has been correlated with a decreased functionality of neutrophils. In the current study, it is suggested that the decreased neutrophil functionality may be induced by the extensive alterations in sex steroid levels occurring around parturition. It was first hypothesized that 17β-estradiol and progesterone influence the viability, apoptosis and necrosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition to the effects on DC, both E2 and PG have been shown to regulate other bovine immune cells including neutrophil phenotype and function and T cell transcription factors indicating these hormones play a larger role in maternal immune regulation and work in concert to generate tolerance (Lamote et al, 2004, Lamote et al, 2006, Maeda et al, 2013. Future research should investigate further functional aspects modulated by these hormones, determine if this relates to changes observed in vivo, and understand the pathways which are regulated by E2 and PR signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the effects on DC, both E2 and PG have been shown to regulate other bovine immune cells including neutrophil phenotype and function and T cell transcription factors indicating these hormones play a larger role in maternal immune regulation and work in concert to generate tolerance (Lamote et al, 2004, Lamote et al, 2006, Maeda et al, 2013. Future research should investigate further functional aspects modulated by these hormones, determine if this relates to changes observed in vivo, and understand the pathways which are regulated by E2 and PR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in dairy cattle showed that in vitro treatments of PG had an effect on lymphocyte transcription factors which may promote T regulatory cell formation, and E2 and PG influence the function of neutrophils. However despite the importance of DC in maternal immune regulation across other species, we lack an understanding of the impact of these hormones on DC (Lamote et al, 2004, Lamote et al, 2006, Maeda et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from three studies support this possibility. Lamote et al [15] observed reduced CD47 expression after blood bovine neutrophils were treated with estrogen for 3 h. Mossuz et al [19] reported an upregulation of CD13 and CD64 antigens after human monoblastic leukemic cells, U937, were exposed to estrogen. Kramer et al [14] showed estrogen downregulation of human monocyte CD16 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse anti-human CD47 (clone BRIC 126), which cross reacts with bovine CD47 [20], mouse anti-bovine CD11b (clone CC126) and their irrelevant control mouse antibody IgG2B; mouse anti-canine CD18 (clone CA1.4E9), which cross reacts with bovine CD18 [3], and its irrelevant control mouse antibody IgG1, secondary antibody polyclonal rabbit anti-mouse IgG-FITC were purchased from Serotec (Oxford, UK) and resuspended in endotoxin-free PBS; goat antimouse IgG1-FITC IgG2b-PE were purchased from Santa Cruz Biotechnology ® (Santa Cruz, CA, USA). The maximal inhibitory dose of each antibody was determined in initial dose-response experiments.…”
Section: Reagentsmentioning
confidence: 99%
“…CD47 is ubiquitously expressed on the plasma membrane [30], and anti-CD47 antibodies have been shown to potently inhibit neutrophil transmigration [22]. The presence and importance of CD47 in the migration of bovine neutrophils (PMN) were recently demonstrated by Lamote et al [20].…”
Section: Introductionmentioning
confidence: 99%